Pengaruh Pengendalian Persedian Bahan Baku dan Proses Produksi terhadap Hasil Produksi: (Survei pada Karyawan Bagian Produksi Konveksi Penjaitan Baju Anak di Cimahi) - Suci Aliana Putri; Suci Putri Lestari; Arif Arif (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
The aim of this research is to determine the magnitude of the influence of Raw Material Inventory Control on Production Results and the influence of the Production Process on Production Results among employees of the Children's Clothing Tailoring Convection in Cimahi. This research is quantitative research using the causality method with a survey approach. The data source used is a primary data source and the data was collected through questionnaires, interviews and observations. In this research, the analytical tool uses multiple linear regression analysis. In the hypothesis testing process, the F test and t test are used. The results of the research show that control of raw material supplies, production processes and production results at the Children's Clothing Tailoring Convection in Cimahi has a very good rating classification. Control of Raw Material Inventory and Production Process simultaneously has a significant effect on the Production Results of the Children's Clothing Tailoring Convection in Cimahi. Partial control of raw material supplies has a significant effect on the production results of the Children's Clothing Tailoring Convection in Cimahi. The partial production process has a significant effect on the production results of the Children's Clothing Tailoring Convection in Cimahi